2015
DOI: 10.3109/07357907.2015.1047509
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vascular Endothelial Growth Factor Receptor 3 Reduces Migration of Gastric Cancer Cells

Abstract: Angiogenesis induced by proangiogenic molecules such as vascular endothelial growth factor (VEGF) is a key process in the progression and metastasis of gastric cancer. In this study, we investigated the role of VEGF-C/VEGF receptor 3 (VEGFR3) axis in cell proliferation and migration/invasion of human gastric cancer cells (hGCCs). VEGF-C did not enhance cell proliferation but increased cell migration/invasion by approximately ∼50% in hGCCs (AGS and SNU-484). MAZ51, a VEGFR3 inhibitor, reduced the VEGF-C-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Furthermore, in our previous study it was demonstrated that SIX1, a developmental transcription factor predicted to represent a potential target gene of miR-23b-3p, may enhance the expression of VEGF-C in OS (2). VEGF-C promotes cervical cancer cell invasion and migration (48), and enhances the metastatic ability of esophageal carcinoma (49), whereas knocking down VEGF-C suppresses gastric cancer cell migration (50). Therefore, VEGF-C was investigated in the present study, and the results demonstrated that miR-23b-3p is associated with decreased expression levels of VEGF-C in U2OS cells.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, in our previous study it was demonstrated that SIX1, a developmental transcription factor predicted to represent a potential target gene of miR-23b-3p, may enhance the expression of VEGF-C in OS (2). VEGF-C promotes cervical cancer cell invasion and migration (48), and enhances the metastatic ability of esophageal carcinoma (49), whereas knocking down VEGF-C suppresses gastric cancer cell migration (50). Therefore, VEGF-C was investigated in the present study, and the results demonstrated that miR-23b-3p is associated with decreased expression levels of VEGF-C in U2OS cells.…”
Section: Discussionmentioning
confidence: 84%
“…ZNF684 (zinc finger protein 684) was increased 2.08‐fold of gene expression, and zinc finger protein X‐linked represents the prominent role in the progression of prostate cancer and may be a promising therapy target for prostate cancer . VEGFB (vascular endothelial growth factor B) was down‐regulated 2.06‐fold of gene expression and VEGFR3 could be a therapeutic target for reducing the metastasis of gastric cancer cells . CDK10 (cyclin‐dependent kinase 10), was down‐regulated 3.22‐fold of gene expression, and the association of low levels of CDK10 with methylation of the CDK10 promoter have been suggested to be a mechanism by which CDK10 expression is reduced in tumors .…”
Section: Discussionmentioning
confidence: 99%
“…CDK2, a member of protein kinase family, significantly modulated abundant events of eukaryotic cell division cycle [ 92 ]. VEGF was known to take a great part in the progression and metastasis of cancers through inducing angiogenesis [ 93 ]. Thus it can be seen that miR-29a adjusted these biological and significant genes and participated in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%